Heat shock protein 70 levels in children with nephrotic syndrome - Bağdagül Aksu; Zeynep Nagehan Yürük Yıldırım; Asuman Gedikbaşı; Alev Yılmaz (The Turkish Journal of Pediatrics)
Background. Idiopathic nephrotic syndrome (NS) is the most prevalent glomerular disease in children. Heat shock protein 70 (HSP70) is synthesized in response to diverse stress factors like infections and oxidative stress. We aimed to evaluate serum and urine levels of HSP70 in children with steroid-sensitive nephrotic syndrome (SSNS) and to assess changes in HSP70 levels with prednisolone treatment. Additionally, we seek to determine whether serum and urine levels of HSP70 can differentiate between frequently relapsing and infrequently relapsing cases in children with SSNS.